2019
DOI: 10.24990/injec.v3i2.226
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Description of Millennial Nurse Administrators’ Perspectives on Leadership and Their Practice Environment

Abstract: Introduction: Millennial nurses are beginning to accept leadership roles and will soon take over governance in the nursing profession and healthcare industry. This study aimed to describe the perspectives on leadership and their practice environment of millennial nurse administrators working in tertiary hospitals in Iloilo City, Philippines. Methods: Eight (8) millennial nurse administrators were purposively chosen. Through a qualitative descriptive inquiry by Sandelowski (2000), data were gathered using semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…Although Asiri, Rohrer, Al-Surimi, Da'ar, & Ahmed (2016) found that most nurses in their study believed that their immediate nursing managers were not displaying the ideal level of transformational leadership behaviors wherein empowerment is central, local studies provide support of the empowering leadership style or behaviors among Filipino nurse managers. For example, Lamasan & Oducado (2018) found that Filipino millennial nurse administrators consider their leadership to be empowering. Correspondingly, Filipino nurses in a tertiary hospital in the Philippines agreed that their nurse managers utilized transformational leadership styles (Lapeña, Tuppal, Loo, Abe, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although Asiri, Rohrer, Al-Surimi, Da'ar, & Ahmed (2016) found that most nurses in their study believed that their immediate nursing managers were not displaying the ideal level of transformational leadership behaviors wherein empowerment is central, local studies provide support of the empowering leadership style or behaviors among Filipino nurse managers. For example, Lamasan & Oducado (2018) found that Filipino millennial nurse administrators consider their leadership to be empowering. Correspondingly, Filipino nurses in a tertiary hospital in the Philippines agreed that their nurse managers utilized transformational leadership styles (Lapeña, Tuppal, Loo, Abe, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Orientated towards people rather than task-driven Maier et al (2015) Have a close connection with their followers Axten (2015) Understanding and non-judgemental Dols, Chargualaf and Martinez (2019) Inclusive and collaborative Maier et al (2015); Paramarta (2018) Accessible and reliable Dols et al (2019) Guiding and empowering Lamasan and Oducado (2018) Committed and dedicated Dols et al (2019) Immediate feedback and recognition Axten (2015); Rony (2019) Individual mentoring Lamasan and Oducado (2018); Omilion-Hodges & Sugg (2019); Rony (2019) Millennials prefer leaders who display a leadership style that shows care for their followers as opposed to meeting their own personal agendas (Long 2017). They prefer leaders who give personal attention to their employees, getting to know them by being more orientated towards people rather than tasks (Maier et al 2015).…”
Section: Elements Authorsmentioning
confidence: 99%
“…Millennials see leaders as guiding and empowering personnel and also as role models (Lamasan & Oducado 2018). They expect leaders to be charismatic by providing their workers with a sense of purpose through encouragement (Grubbström & Lopez 2018).…”
Section: Elements Authorsmentioning
confidence: 99%
“…The nurses included in this survey were generally young, not older than 35 years old. These nurses belong to the millennial generation and are believed to be the largest cohort in the current nursing workforce (Lamasan & Oducado, 2018). Attention must be given to younger nurses, like new graduate nurses, as they were found to have limited CPD participation (Ubas-Sumagaysay & Oducado, 2020).…”
Section: Types Of Cpdmentioning
confidence: 99%